Biblio files : a history of the Regina Public Library - Campbell, Anne, 1938-; Mah, Jeannie; Birley, Susan, 1955- (University of Regina Press, 2017)
"For over 100 years, the Regina Public Library has served its community with innovative programming, but the full story of this venerable institution has never been told-until now. From the efforts of its first librarian who ensured immigrants could access books in their own languages, to the present day as an active community hub, the library has been responsible for many groundbreaking Canadian firsts. The Regina Public Library implemented the country's first fully automated library system, established the first writer-in-residence program, pioneered English as a Second Language classes, hosted Indigenous storytelling circles, and was instrumental in developing a single, one-card system for all of Saskatchewan. With contributions from community members, Biblio Files covers the library's entire history and demonstrates why it is such a beloved and necessary institution."--